GRAVITY-MAGNETIC SURVEY FOR THE OIL AND GAS PROSPECTING IN AZERBAIJAN AND UKRAINE - Gadirov, V.; Menshov, O.; Kuderavets, R.; Gadirov, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The hydrocarbon deposits located in various oil- and gas-bearing regions of Azerbaijan and Ukraine manifest in the gravitational and magnetic fields. The hydrocarbons have the perceptible influence on the magnetic susceptibility of the near-surface geological sections and soil. The examples in Azerbaijan are presented by Muradkhanli and Jafarli oil and gas deposits. The intensity of the local magnetic field is characterized by the negative anomalies of about 30–40 nT. Anomalous effect of gravity-magnetic fields is more dependent on the capacity of oil and gas deposits, rather than on their depth. Deep-seated oil and gas deposits in the gravity-magnetic fields are displayed due to the additional anomalous effect of the subvertical zones of the area of the deposit. The results of the magnetic field and soil magnetism study of the hydrocarbon deposits in Ukraine are exemplified by Vizomlanske and Sudova-Vishna oil and gas fields. Taking into account the background of the regional magnetic field anomalies, the areas where the field is considerably changed by local minimums with an amplitude of about 2–8 nT and a width of 1–3 km were identified. At the edges of these anomalous zones the short-period maximums with the intensity of 10–20 nT were registered. The increase of the soil magnetic susceptibility and high magnetic susceptibility dispersion are related to the formation of autogenic iron oxides and sulphides under the influence of hydrocarbons microseepages over a reservoir. These magnetic minerals are diagenetic magnetite, maghemite, and pyrrhotite. To increase the unambiguous interpretation effectiveness and quality of the magnetic field, soil magnetism, and the nature of local magnetic anomalies over the hydrocarbon structures, additional data about other geophysical, geochemical, lithological, neotectonic and soil science studies should be used by researchers.
Keywords: magnetometry; gravity survey; magnetic susceptibility; soil; hydrocarbons